STUDENTS’ ATTITUDES TOWARD CALCULUS: A PRELIMINARY STUDY AMONG DIPLOMA STUDENTS AT UNIVERSITI PUTRA MALAYSIA (Sains Humanika, 2005)
A preliminary study was conducted among 62 diploma students at Universiti Putra Malaysia (UPM) to (1) assess their attitudes toward Calculus, (2) determine the difference in attitudes scores between males and females and (3) assess the relationship between students, attitudes toward Calculus and their prior Mathematics achievement. Attitude was measured in cognitive, affective, and behavioural domains. The findings showed that a high percentage of students did not have positive attitudes toward Calculus. There was a statistical significant difference in the mean scores for males and females in the Calculus attitudes scale. Specifically, statistical significant differences were detected between males and females in two attitude domains: cognitive and behavioural. The correlation between students’ attitudes toward Calculus and Mathematics grade was low and not statistically significant. In general, this study revealed that diploma students in UPM have different levels of attitudes toward Calculus. This information would be helpful to Mathematics lecturers when they conduct their lectures.
Keywords: Attitudes; Calculus; diploma students